Review of drug-food interactions based on medications used by users of a Basic Health Unit in Sarandi, Parana - Silva, Everton Cristian Alves da; Costa, Marco Antonio; Moura-Costa, Gislaine Franco de (Revista Uningá, 2025)
Drug-food interactions do exist and occur often in the population, making it difficult for patients to adhere to the proposed treatment, which means the analysis of this problem is essential. This study aimed to review drug and food interactions based on the medicines used by users of a Basic Health Unit in Sarandi, Paraná, and their dietary routine. To this end, a cross-sectional study was conducted at the Basic Health Unit in question, where a semi-structured questionnaire was applied on the medicines used and schedules, dietary routine, socioeconomic and health data of patients. The databases used for research on drug-food interactions were Micromedex, Drugs.com and DrugBank. In this study, we observed that many medicines used by patients may present interactions with food frequently consumed by the population. There is information in the literature that should be known by health professionals to guide patients on the best way to take their medicines, so as to avoid undesirable interactions. The pharmacist is the proper professional to carry out pharmacotherapeutic monitoring, as well as to guide the patient regarding the best time to administer medicines in relation to meal times, avoiding negative impacts on therapeutic efficacy and patient safety.